2022
DOI: 10.1371/journal.pone.0263576
|View full text |Cite
|
Sign up to set email alerts
|

Intensive grazing alters the diversity, composition and structure of plant-pollinator interaction networks in Central European grasslands

Abstract: Complex socio-economic, political and demographic factors have driven the increased conversion of Europe’s semi-natural grasslands to intensive pastures. This trend is particularly strong in some of the most biodiverse regions of the continent, such as Central and Eastern Europe. Intensive grazing is known to decrease species diversity and alter the composition of plant and insect communities. Comparatively little is known, however, about how intensive grazing influences plant functional traits related to poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 85 publications
1
17
1
Order By: Relevance
“…To stop and reverse abandonment, grazing is often seen as an essential tool for nature conservation purposes ( Kapfer, 2019 , Stewart and Pullin, 2008 ). However, whereas intensifying land use of a nearly abandoned pasture might result in positive effects, intensification of an extensively managed pasture might cause declines ( Rakosy et al, 2022 ). Thus, understanding the consequences of different livestock densities is of major importance ( Batáry et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To stop and reverse abandonment, grazing is often seen as an essential tool for nature conservation purposes ( Kapfer, 2019 , Stewart and Pullin, 2008 ). However, whereas intensifying land use of a nearly abandoned pasture might result in positive effects, intensification of an extensively managed pasture might cause declines ( Rakosy et al, 2022 ). Thus, understanding the consequences of different livestock densities is of major importance ( Batáry et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…in immature stages. Moreover, high management intensity has been shown to cause negative indirect effects as well, such as a homogenisation of plant communities and a dominance of grasses, resulting in a loss of food plants and nectar sources for insects ( Rakosy et al, 2022 , WallisDeVries et al, 2016 , WallisDeVries and Raemakers, 2001 ). Although we found a linear negative relationship between species richness and herbivore stocking density, negative effects can be expected on the opposite extreme of the gradient as well, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In temperate grasslands, abundant flower‐visiting insects that play an important role in pollination are mainly social and solitary wild bees (Apoidea: Anthophila) and other hymenopterans, hoverflies (Diptera: Syrphidae) and several other dipteran families, several beetle (Coleoptera) families, as well as moths and butterflies (Lepidoptera) (Forup & Memmott, 2005; Michelot‐Antalik et al ., 2021; Rakosy et al ., 2022). In addition, several vertebrate taxa, and in particular nectarivorous birds, are important pollinators in temperate grasslands [e.g.…”
Section: Landscape‐scale Land‐use Effects On Pollinators In Grasslandsmentioning
confidence: 99%
“…It is thus critical to monitor plant-pollinator interactions and to understand the factors that cause these interactions to change across space and time. As many species of pollinating insects cannot be identified on sight, most studies quantifying plant-pollinator interactions capture insects that are observed to visit flowers and identifying them later using microscopy (e.g., Motivans Švara et al 2021; Rakosy et al 2022) or DNA barcoding (Creedy et al 2020). While these methods are accurate and can provide museum specimens that are valuable for a wide variety of research purposes (Rakosy et al 2023), they are time consuming, costly to scale, and require expert knowledge in insect taxonomy or barcoding.…”
Section: Introductionmentioning
confidence: 99%